Management of liver trauma after blunt trauma abdomen: Management of liver trauma after blunt trauma abdomen - Abdul Manan; khan, Ashar Ahmad; Ahmad, Irfan; Qadir, Abdul; Usman, Muhammad; Athar, Saim (Medical Journal of South Punjab, 2023)
Objective: is to investigate the better management plan for liver injury after blunt trauma abdomen according the latest classification system. Methodology: Prospective study was conducted at department of general surgery Nishtar hospital Multan from 31st July 2022 to 30th June 2023 in one year duration. A total of 70 patients with liver injury diagnosed intraoperatively or by CT scan were enrolled in the study. Main variables of study were Moore score, Mirvis score, mechanism of injury, organ affected and type of injury according to classification. SPSS version 23 was used for data analysis. Results: Frontal car accident was the most common trauma mechanisms in type A patients 51.6% and complex traffic accident was the most common trauma mechanisms in type B patients 38.5%. High-energy trauma in type A and type B patients was 80.6% and 89.7% patients respectively. Further, demographic and baseline characteristics of type A and type B patients were almost equal, (p>0.010). Conclusion: The management of liver injury has shift towards a more individualized approach depending on the localization of parenchymal disruption (damage to the liver tissue) and may correlate with the mechanism of trauma. Type of injury is the correlation with necessity of surgical management.